PENERAPAN PEMBELAJARAN DIGITAL GAME BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATERI STATISTIKA PADA SISWA KELAS VIII SMPN 2 JEMBER - Abdul Halim Fathani; Kholada Sa’diyah (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
This article is discussed about the application of Digital Game Based Learning (DGBL) learning using Gimkit as a learning medium. The problem that underlies the application of this learning is the lack of problem-solving skills in students so that it has an impact on low learning outcomes. This can be seen from the calculation of the average score of PTS and PAS, where the number of students who get scores above the minimum completeness criteria (KKM = 75) is only 13 students or 39.4% of the total number of students, namely 33. In addition, the average score obtained by students is also still low at 68.6. Therefore, the purpose of this study is to improve problem-solving skills in grade 8A students of SMPN 2 Jember. This study uses the Kemmis & McTaggart model which consists of four components, namely planning, action and observation, and reflection. The four components are seen as one cycle, while this study consists of three cycles. The results of this study show that with the application of Digital Game Based Learning learning, the problem-solving ability of students becomes more improved, this is seen from the results of pretests and postest given to students during learning. The percentage of completeness in cycle 1 is 50%, then increases in the second cycle to 94% and in cycle 3 to 100%. Based on the results of the study, it can be concluded that the application of digital game base learning can improve problem solving skills in grade 8A students of SMPN 2 Jember.